Superalloys - Characterization, Usage and Recycling - Kollova, Alexandra; Pauerova, Katarina (Manufacturing Technology Journal, 2022)
Superalloys are a group of alloys developed for use during long-term heat exposure above 650 °C. Properties and applications of superalloys are described in the present work. The work includes statis-tics about superalloys demand, market value and the current price. Division of superalloys according to basic element is mentioned. Nickel-based superalloys are further divided into two groups accord-ing to their use. Afterwards, the paper is focused mainly on nickel-based superalloys. Examples of nickel-based superalloys are listed in the work. Recycling possibilities of nickel-based superalloys are stated and analysed. General scheme of processing nickel-based superalloy scrap with regard to the content of rhenium is proposed and shortly discussed. The best-known companies dealing with sup-eralloy scrap recycling are mentioned further.
Keywords: Superalloys; Nickel; Recycling